2000
DOI: 10.1021/jp002697g
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation Kinetics of Hydroxyapatite Revealed by the Continuous-Angle Laser Light-Scattering Technique

Abstract: The precipitation kinetics of hydroxyapatite from calcium phosphate aggregates was investigated by the continuous-angle laser light-scattering technique in the systems CaCl 2 -H 3 PO 4 -H 2 O and KCl-CaCl 2 -H 3 PO 4 -H 2 O at 25 °C. The apparent molecular weights of aggregates increased with time, and precipitation of hydroxyapatite occurred in both systems. However, the radius of gyration of the aggregate was almost constant in the former system, while it increased with the increase of the molecular weight i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
63
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(69 citation statements)
references
References 39 publications
6
63
0
Order By: Relevance
“…Earlier studies that used conditions similar to the ones we used (1.0 mM CaCl 2 and 2.5 mM KH 2 PO 4 , pH 8.0 at 25°C) revealed that ACP particles with radii ranging from 200 to 500 nm formed first in the solution (13,17). Our conditions also produced initial particles having an R g of Ϸ340 nm and a d f of Ϸ1.8, irrespective of the presence of the #64.…”
Section: Resultssupporting
confidence: 62%
See 3 more Smart Citations
“…Earlier studies that used conditions similar to the ones we used (1.0 mM CaCl 2 and 2.5 mM KH 2 PO 4 , pH 8.0 at 25°C) revealed that ACP particles with radii ranging from 200 to 500 nm formed first in the solution (13,17). Our conditions also produced initial particles having an R g of Ϸ340 nm and a d f of Ϸ1.8, irrespective of the presence of the #64.…”
Section: Resultssupporting
confidence: 62%
“…Time-resolved static light scattering (TR-SLS) measurements enabled us to observe changes in the apparent molecular mass (M w ), gyration radius (R g ), and fractal dimension (d f ) of calcium phosphate particles at an early stage during HAP formation (16,17). Earlier studies that used conditions similar to the ones we used (1.0 mM CaCl 2 and 2.5 mM KH 2 PO 4 , pH 8.0 at 25°C) revealed that ACP particles with radii ranging from 200 to 500 nm formed first in the solution (13,17).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The association of cellobiohydrolase molecules after the protein solution (containing cellobiose) was mixed with the crystallization buffer at a volume ratio of 1:1 was observed using a multi-angle SLS detector [28][29][30][31][32]. The concentration of cellobiohydrolase in the mixed solution was 7 mg/mL and that of lithium sulfate was 1.25 M. The scattering intensities at q from 20˚ to 150˚ with a step of 1˚ were simultaneously measured over time at intervals of 3 s for each R(cb/ce) condition.…”
Section: Dynamic and Time-resolved Static Light Scattering Measurementsmentioning
confidence: 99%